Study on sodium nitrate as alternative admixture for opc based binder - Norul Diyana, Mohd Ghazali (2014)
Ordinary concrete refers to the ordinary Portland cement as a cementing material with water and admixtures which sometimes is added to a certain proportions according to the strength required and the function to be fulfilled. Nevertheless, the presence of high sodium Nitrate content in the source material can reduce the performance of cement paste binder, particularly in terms of its workability performance. This research studied the effect of sodium nitrate as the alternative admixture in Ordinary Portland Cement (OPC) based binder. Based on vicat setting time result, and these materials behave oppositely in cement paste and has an accelerating effect. Furthermore 90 samples a size 50mm x 50mm x 50mm, will be tested during the study where the test that carried out to measure the workability test, compressive strength test and porosity test at 1 day, 7 days and 28 days. In addition admixture Sodium Nitrate is 0.1%, 0.2%, 0.3%, 0.4% and 0.5% in cement paste. However, these results have presented an encouraging prospect for material to be developed as the admixture for cement paste.